Control of porcine reproductive and respiratory syndrome (PRRS) through genetic improvements in disease resistance and tolerance - Rowland, Raymond; Lunney, Joan; Dekkers, Jack (Frontiers in Genetics, 2012)
Infections caused by porcine reproductive and respiratory syndrome virus (PRRSV) have a severe economic impact on pig production in North America, Europe and Asia. The emergence and eventual predominance of PRRS in the 1990s are the likely result of changes in the pork industry initiated in the late 1970s, which allowed the virus to occupy a unique niche within a modern commercial production system. PRRSV infection is responsible for severe clinical disease, but can maintain a life-long subclinical infection, as well as participate in several polymicrobial syndromes. Current vaccines lessen clinical signs, but are of limited use for disease control and elimination. The relatively poor protective immunity following vaccination is a function of the virus’s capacity to generate a large degree of genetic diversity, combined with several strategies to evade innate and adaptive immune responses. In 2007, the PRRS Host Genetics consortium (PHGC) was established to explore the role of host genetics as as an avenue for PRRS control. The PHGC model for PRRS incorporates the experimental infection of large numbers of growing pigs and has created the opportunity to study experimental PRRSV infection at the population level. The results show that pigs can be placed into distinct phenotypic groups, including pigs that show resistance or pigs that exhibit “tolerance” to infection. Tolerance is best illustrated by pigs that gain weight normally in the face of a relatively high virus load. Genome-wide association analysis has identified a region on chromosome 4 (SSC4) correlated with resistance; i.e., higher weight gain combined with lower virus load. The genomic region is near a family of genes involved in innate immunity. These results create the opportunity to develop breeding programs that will produce pigs with increased resistance to PRRS. The identification of genomic markers involved in tolerance will likely prove more difficult, primarily because tolerance as a mechani